The Use of Methanolic Extract of Persian Gulf Sea Cucumber, Holothuria, as Potential Anti-Cancer Agents - Seyed Razi, Nina; Arast, Yalda; Nazemi, Melika; Pourahmad, Jalal (International Pharmacy Acta, 2018)
Hepatocellular carcinoma (HCC) is the fifth most malignant of liver cancer globally. Melanoma is also a highly aggressive and deadly cancer with a poor prognosis given its drug resistance.A defect in apoptosis pathway is one of the key mechanisms that contribute to drug resistance in cancer. An important sea marine animal is the Holothuria, also known as the sea cucumber, which has various pharmacological activities. Scientists have begun to further investigate on the natural bioactive compounds found in marine animals showing anti-inflammatory and anti-cancer properties. H. sabra and H. parva, sea cucumbers are known to show the mentioned properties. Cancerous induced animals were applied for mitochondrial investigations. The mitochondria isolated from Hepatocytes and melanoma cells via differential centrifuges was treated with various concentrations (250, 500 and 1000 µg/ml) of metanolic extract of H. parva and H. sabra. Reactive oxygen species (ROS) formation, mitochondrial swelling, mitochondrial membrane potential (MMP) and cytochrome c release resulting from the selective toxicity of various dilution of methanolic extract of H. sabra and H. parva on mitochondria isolated from cancerous induced animals were determined. Our results show that different concentrations (250, 500 and 1000µg/ml) of themethanolicextract significantly (p<0.05) induce reactive oxygen species (ROS) formation and mitochondrial swelling, decreased mitochondrial membrane potential (MMP) disruption and increased cytochrome c release only in HCC mitochondria and melanoma mitochondria, in a time-and concentration dependent manner (In comparison to the control group). Our study suggest that given bioactive compounds found in mentioned sea cucumbers can potentially introduced as anti-cancer molecules. Further studies such as molecular identification, in vivo experiments and clinical trials can confirm these results.